1998
DOI: 10.1590/s0100-879x1998000600017
|View full text |Cite
|
Sign up to set email alerts
|

Acute blood volume expansion delays the gastrointestinal transit of a charcoal meal in awake rats

Abstract: The present study evaluates the effect of blood volume expansion on the gastrointestinal transit of a charchoal meal (2.5 ml of an aqueous suspension consisting of 5% charcoal and 5% gum arabic) in awake male Wistar rats (200-270 g). On the day before the experiments, the rats were anesthetized with ether, submitted to left jugular vein cannulation and fasted with water ad libitum until 2 h before the gastrointestinal transit measurement. Blood volume expansion by iv infusion of 1 ml/min Ringer bicarbonate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…We have previously reported that acute BV expansion significantly delays the GE of liquid as well as the gastrointestinal transit in awake rats 5 , 8 –10 – an effect which varied according to the amount of infused volume. Since the greatest GE delay we observed in our previous studies was obtained in rats submitted to a BV expansion equivalent to 5% body weight, 9 we fixed this level of BV expansion in the present study in order to investigate the neural mechanisms involved in the GE delay elicited by acute BV expansion.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We have previously reported that acute BV expansion significantly delays the GE of liquid as well as the gastrointestinal transit in awake rats 5 , 8 –10 – an effect which varied according to the amount of infused volume. Since the greatest GE delay we observed in our previous studies was obtained in rats submitted to a BV expansion equivalent to 5% body weight, 9 we fixed this level of BV expansion in the present study in order to investigate the neural mechanisms involved in the GE delay elicited by acute BV expansion.…”
Section: Discussionmentioning
confidence: 95%
“…This BV overload protocol has been extensively utilized in our previous studies, both in anaesthetized rats and in awake rats 6 . 8 –10 For investigating neural mechanisms, separate groups of rats were previously submitted to a drug pretreatment or a surgical procedure. In all protocols, the animals were killed at a fixed time interval (10 min) after liquid meal gavage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the proximal stomach tonus drives gastric fluid emptying, BV changes may modify the flow through the gastroduodenal segment (15). However, the gastric emptying rate and the gastrointestinal transit of a liquid meal in awake rats are decreased by hypervolemia and increased after hypovolemia (16,17). This apparent discrepancy can be understood if one considers the breaking effect of duodenal motility on gastric emptying (15).…”
mentioning
confidence: 99%